A pilot case-control study of the association of vitamin D-related gene variants with peri-implantitis - Magić, Marko; Lazić, Zoran; Jovandić, Stevo; Rakašević, Dragana; Zeljić, Katarina (Archives of Biological Sciences, 2025)
Paper description: This pilot case-control study explored whether genetic variants in vitamin D-related genes, vitamin D receptor (VDR), retinoid X receptor alpha (RXRA), and cytochrome P450 family 27 subfamily B member 1 (CYP27B1), can serve as risk markers for peri-implantitis development. The study enrolled 82 patients with dental implants, 30 had peri-implantitis, and 52 exhibited healthy peri-implant tissues. Genetic variants (VDR rs2228570, RXRA rs3118523, rs7864987, and CYP27B1 rs4646536) were analyzed using Real-Time PCR to determine their association with peri-implantitis. No significant differences in genotype distributions between peri-implantitis and healthy groups were observed, suggesting that genetic variants are unreliable markers for peri-implantitis susceptibility. Abstract: This pilot case-control study investigated whether variants in vitamin D-related genes can be used to predict the occurrence of peri-implantitis. Eighty-two patients with at least one dental implant were enrolled. Thirty patients (36.6%) were diagnosed with peri-implantitis, whereas 52 (63.4%) had healthy peri-implant tissues. Clinical parameters, risk factors (history of periodontitis, smoking), and genetic factors were assessed. A buccal mucosa swab was taken for DNA analysis. Four variants in three vitamin D-related genes, VDR (rs2228570), retinoid X receptor alpha (RXRA) (rs3118523, rs7864987), and cytochrome P450 family 27 subfamily B member 1 (CYP27B1) (rs4646536) were genotyped by real-time PCR. There was no difference in the genotype distribution of the variants VDR rs2228570 (P=0.410), RXRA rs3118523, rs7864987 (P=0.789 and P=0.144, respectively), and CYP27B1 rs4646536 (P=0.562) between patients with healthy peri-implant tissues and those affected by peri-implantitis. History of periodontitis, a modified plaque index (mPI), modified bleeding index (mBI), peri-implant pocket depth, and implant location were associated with peri-implantitis incidence. In patients with peri-implantitis, CYP27B1 rs4646536 was associated with mBI (P=0.040), and RXRA rs7864987 was associated with implant position (P=0.009). We conclude that the variants of vitamin D-related genes, VDR, RXRA, and CYP27B1, cannot be used as molecular markers for peri-implantitis.